A la recherche de la dimension sociale du développement durable - Léa Sébastien; Christian Brodhag (Développement Durable et Territoires)
In a broader sense, sustainable development aims to enhance a state of harmony between human beings and between man and nature (CMED, 1988). Yes, but if studies on man and nature relationships are frequently conducted, those on harmony between human beings remain pretty rare. On a territory, how can we value this social harmony ? After a few recall of the notions of sustainable development, negotiation and conservation, the last part will present the Actor in 4 dimensions, a methodological proposition which aims to facilitate integrated and participatory management approaches toward natural resources.